Negative emotions in informal feedback: The benefits of disappointment and drawbacks of anger - Johnson, Genevieve; Connelly, S. (2014)
Using the emotions as social information (EASI) model, this study investigated the emotional, attitudinal and behavioral reactions to failure feedback by manipulating negative emotional displays (angry, disappointed or none) and the position level and relational distance of the feedback source. Undergraduate students (N = 260) responded to an organizational failure feedback vignette and completed a subsequent performance task. Results demonstrated that guilt was the complementary emotional experience following displays of disappointment, while reciprocal anger followed displays of anger. These emotional reactions served as important mediators between the emotional displays paired with the feedback message and participant responses of social behaviors, creative task performance and perceptions of the feedback source. In addition, our findings indicated that negative emotions can have positive organizational and interpersonal outcomes. Guilt in response to disappointed displays resulted in beneficial behaviors and attitudes, while anger in response to angry displays was socially detrimental. The emotion displayed during feedback provision also served as a consistent contextual factor that did not interact with the position level or relational distance of the feedback source to impact behavioral and attitudinal reactions. Overall, this study indicates that discrete negative emotions have unique social-functional properties that require further investigation.